Konseling Eksistensial: Suatu Proses Menemukan Makna Hidup - Triyono, Y. (Jurnal Orientasi Baru, 2010)
Human life is motivated by searching of meaning. Life without meaning is unbearable. This is the condition where human being undergoes existential vacuum. Logoteraphy, as existential counseling and psychotherapy, helps human being to solve this existential problem. There are three ways to reach the meaning of life: (1) creative values, (2) experiential values, and (3) attitudinal values. Logoteraphy fundamentally believes that human being has positive freedom and responsibility. Based on those two qualities human being can transcend their condition: though they are not free from certain conditions, they have freedom to take a stand in every condition. The meaning of life can be experienced in all conditions, also in the situation of incurable sufferings.